THE RESPONSE OF QUALITATIVE AND QUANTITATIVE CHARACTERISTICS OF GERMAN CHAMOMILE (MATRICARIA RECUTITA L ) TO THE FERTILIZING IMPACTS OF VERMICOMPOST - Hoseinzadeh, P.; Hatamzadeh, A.; Tavakol, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Chamomile (Matricaria recutita L.) is an important medicinal plant and its multi-therapeutic, cosmetic and nutritional values have been established through years of traditional and scientific application. In order to examine the impact of organic agriculture on the plant’s qualitative and quantitative characteristics along with producing a healthy plant as a source of human health products, while considering preservation of natural resources, this experiment was designed to determine the influence of vermicompost derived from cattle manure and crop residues without the application of chemical fertilizers on the essential oil and phenolic compounds of chamomile in temperate climate condition. The results represented that different vermicompost levels (0, 4, 8, 12 &16 t ha-1) improved and enhanced plant growth, plant height, number of shoots and flower accumulative dry matter through increasing fertilization levels. As a result, the implementation of 16 t ha-1 had the most significant effect on the mentioned characteristics. Oil yield was increased by comparing to the control (non-fertilized). Analysis of chamomile volatile constituents by GC and GC-MS, identified fifty-one components, which represented 97.5% of the oil. In addition, the highest contents of main constituents, including bisabolol oxide A (35.5%) and B (8.6%), β-farnesene (4.1%), and chamazulene (17.5%), were achieved from the implementation of 16 t ha-1 treatment. HPLC analysis of chamomile extract confirmed apigenin 7-O-glucoside as the major oil constituent in all treatments. Although the 16 t ha-1 treatment had the highest impact on evaluated characteristics, there were no significant differences between 12 t h-1 and 16 t h-1 treatments. [1]Mann, C. and E.J. Staba. 1986. The chemistry, pharmacology, and commercial formulations of chamomile, p. 235-280. In: L.E. Craker and J.E. Simon (eds). Herbs, Spices, and Medicinal Plants. Recent Advances in Botany, Horticulture, and Pharmacology. Food Products Press. 1, p: 235-280.